TRPV6 channel function is involved in endometrial epithelial cell Ca2+ signaling and female mouse fecundity - Sota, Adela; Beck, Andreas; Wartenberg, Philipp; Gehl, Anna-Lena; Winter, Manuel; Wissenbach, Ulrich; Freichel, Marc; Meyer, Markus R.; Boehm, Ulrich; Flockerzi, Veit; Fecher-Trost, Claudia; Weißgerber, Petra (Cellular and molecular life sciences, 2025)
The Ca2+-selective transient receptor potential vanilloid 6 (TRPV6) channel plays a fundamental role in the female and male murine reproductive system. We have previously shown that TRPV6 is essential for male fertility, and necessary for a proper placental Ca2+ transport, embryonic bone development and calcification, as well as for extracellular matrix formation in the placental labyrinth. Here, we show that lack of functional TRPV6 results in impaired fecundity in female mice with increased latency to first pregnancy, longer interpregnancy intervals and fewer and smaller litters. In mouse endometrium the TRPV6 protein is expressed in epithelial cells (MEECs). Using patch clamp recording and Ca2+ imaging, we show TRPV6-dependent whole-cell currents and that TRPV6 contributes to cytoplasmic Ca2+ signaling in MEECs. MEECs lacking functional TRPV6 Ca2+ channels reveal a significantly reduced frequency of spontaneous cytosolic Ca2+ oscillations, shown in isolated cells and in situ in whole mount uterus preparations. Our results reveal a previously unknown physiological role for TRPV6 in the regulation of endometrial Ca2+ homeostasis and its impact on female fecundity in mice, providing a molecular and cellular framework for further investigation of reproductive disorders, such as those associated with defective Ca2+ regulation in women.